Composing Cultural Connections: Exploring Tensions of Creating Composite Ethnodramatic Characters - Danielle Hradsky (2024)
This article discusses tensions of creating composite characters in ethnodramas, with particular focus on characters’ cultural identities. Six teacher characters were composed from 12 research participants for Connections, an ethnodrama that highlights the importance of cultural identity when engaging with teaching for reconciliation between First Nations and non-Indigenous Australians. This article presents the author’s ethnodrama methodology, as well as excerpts from the ethnodrama itself, before unpacking complexities related to composing characters’ cultural identities. It is suggested that composing characters protects participant anonymity but opens new possibilities and uncertainties that should be carefully considered as part of the ethnodramatic process.